Faktor-Faktor Yang Berhubungan Dengan Tingkat Kecemasan Menjelang Persalinan Pada Ibu Primigravida Trimester III di Wilayah Kerja Puskesmas Lubuk Buaya Padang Tahun 2012 : Factors Associated with Anxiety Level Toward Childbirth in Primigravida Trimester III Mothers in the Work Area Lubuk Buaya Padang Health Center in 2012 - Reska Handayani (Fakultas Keperawatan Universitas Andalas, 2015)
A natural pregnancy occurs in women of productive, but their ignorance behaviors, information relating to reproduction would cause anxiety in itself. In Indonesian there are 373 million people of pregnant women who experience anxiety in the face of labor there are as many as 107 million people (28.7%). While the entire population on the island of Sumatra there were 679 765 pregnant women who experience anxiety in the face of labor 355 873 people (52.3%) (MOH, 2008). The purpose of this study was to determine the factors associated with levels of anxiety in the mother before delivery in the third trimester primigravida Work Area Health Center Lubuk Buaya Padang 2012.This research method is descriptive analytic cross sectional study approach. Population in this study were all primigravida mother who comes to prenatal care in the month of January to March 2012 in the working area of Padang in Lubuk Buaya health center with a population of 177 people, and a sample of 64 people , with sampling done by purposive sampling. When the study started from the month of March to July 2012.The results obtained are of respondents who have anxiety (70.3%), age of the respondents are not at risk (87.5%), respondents in the category of higher education (82.8%), support a good husband (71.9%), support both families (76.6%). After statistical tests there was a significant association between age with the level of anxiety (p = 0.000), education level of anxiety (p = 0.005), husband support the level of anxiety (p = 0.000), support for families with high levels of anxiety (p = 0.000). Based on the results of the study suggested the Lubuk Buaya health center to make it more complete, specific and efficient in performing the service by providing counseling on pregnancy and childbirth to reduce the number of anxiety before delivery.